Real-world survival and prognostic factors in WHO 2021 classified gliomas treated with chemo-radiotherapy - Bilski, Mateusz; Noël, Georges; Smółka, Krzysztof; Kuncewicz, Katarzyna; Kuźnicki, Wojciech; Feuvret, Loic; Korab, Katarzyna; Peszyńska-Piorun, Magdalena; Korona, Paweł; Baranowska, Izabela; Suleja, Agata; Le Fevre, Clara; et al. (Scientific reports, 2025)
The 2021 WHO glioma classification integrates molecular profiling, but outcome data for these patients are limited. We retrospectively analyzed 179 patients (median age 53) with WHO 2021-classified gliomas (grade 2: n = 45, grade 3: n = 51, grade 4: n = 83) treated with surgery and radio(chemo)therapy across four centers in Poland and France. Chemotherapy was administered to 74.9% of patients, with a median radiotherapy dose of 60 Gy (range 32.5–80 Gy). IDH1/2 mutations were identified in 55.3% and 1p/19q codeletion in 22.4%. Patients with IDH1/2 mutations had significantly longer progression-free survival (PFS, 7.7 vs. 1.0 years) and overall survival (OS, 8.2 vs. 2.5 years), both p < 0.01. 1p/19q codeletion was associated with prolonged PFS (7.7 vs. 1.6 years, p < 0.01). In grade 3 gliomas, chemotherapy improved PFS (6.8 vs. 3.6 years) and OS (6.9 vs. 3.9 years), both p < 0.01. Leukopenia grade 0–2 correlated with better PFS (3.6 vs. 1.2 years, p = 0.02) and OS (7.2 vs. 3.2 years, p = 0.04). Absolute lymphocyte count ≤ 1 × 10 3 /mm 3 predicted worse OS (5.3 vs. 8.7 years, p = 0.0043). CTV < 127 cm 3 predicted longer OS in grade 4 gliomas (3.2 vs. 1.7 years, p = 0.012). Our findings provide new real-world evidence on survival and prognostic factors in this population, for which contemporary RWE and OS/PFS data remain scarce.